Arabinogalactan, Bifidobacterium longum, and Faecalibacterium prausnitzii improve insulin resistance in high‐fat diet‐induced C57BL/6J mice. Issue 1 (8th May 2022) - He, Huijun; Sun, Yonggan; Zhang, Shanshan; Zhang, Hao; Su, Wenwen; Guo, Zheyu; Zhang, Yanli; Wen, Jiajia; Li, Xiajialong; Hu, Jielun; Nie, Shaoping
Abstract: The occurrence and development of insulin resistance (IR) are usually related to the change of gut microbiota. Our previous study showed that arabinogalactan (AG) could selectively increase the relative abundance of Bifidobacterium longum and Faecalibacterium prausnitzii in in vitro fermentation. However, their effect on IR remains unclear. In the current study, we investigated the effects of AG, B. longum, F. prausnitzii and their combinations on insulin‐resistant mice. Intake of AG and those two strains reduced the body weight, fat accumulation, and homeostasis model assessment of IR of the mice with IR, and decreased the level of serum glucose, insulin, and lipids. Meanwhile, they could alleviate the injury of the liver. Moreover, AG, B. longum, and F. prausnitzii regulated the production of short‐chain fatty acids and elevated the abundance of gut probiotics such as Lactobacillus, Lactococcus, and Bifidobacterium . However, the effect of giving only AG or a single strain was weaker than the combination of AG, B. longum, and F. prausnitzii . Our study attempted to find a new way to prevent the development of type 2 diabetes in the early stage and provided evidence for new therapy against IR with a combination of prebiotics and two bacterial strains of gut origin. Abstract : Arabinogalactan, Bifidobacterium longum, and Faecalibacterium prausnitzii improve insulin resistance in high‐fat diet mice.